Community assembly and co-occurrence network complexity of interstitial microbial communities in the Arctic (investigation of ciliates in the White Sea intertidal zone). (March 2023) - Lu, Xiaoteng; Yu, Xiaowen; Burkovsky, Igor; Esaulov, Anton; Li, Xiaolei; Jiang, Yong; Mazei, Yuri
Abstract: Arctic coastal ecosystems play a major role in global environmental system and have been altered significantly by climate changes. To better understanding the response of marine coastal ecosystems towards rapid Arctic climate changes, we examined the variation in diversity and community structure and provided insights into the co-occurrence network and community assembly of interstitial ciliates in the Kandalaksha Gulf of the White Sea from 2009 to 2019. Co-occurrence networks analysis indicated considerably high ration of positive correlations within a community that indicated low competition between interstitial ciliate species. Furthermore, we found that contribution of stochastic processes to the ciliate community assembly was insignificant. Compare with earlier data from the same ecosystem obtained in 1980s–1990s, the role of competitive factors is decreasing, and communities are becoming more spatially and temporally homogeneous. This community simplification is likely due to the response of the entire intertidal ecosystem to global climate change in Arctic. Highlights: The response of marine coastal ecosystems towards rapid Arctic climate changes Diversity and community structure of interstitial ciliates in White Sea Co-occurrence networks indicated low competition between interstitial ciliate species. Stochastic processes to the ciliate community assembly were not significant.